Sistem navigasi berasaskan algoritma Dijkstra di dalam persekitaran tiga dimensi - Ujang, Muhamad Uznir (2008)
Navigation is an important aspect in some areas such as industrial transportation, emergency navigation and also navigation planning. Network analysis in navigation process can minimize transportation cost, disaster or accident impact and also it can provide right decision for the best route in certain situations. Dijkstra's algorithm is one of the algorithms that could be used in network analysis process especially for 2D shortest route data. Network analysis for three-dimensional (3D) network is required when it involves navigation inside a multi-level building. Current Geographical Information System (GIS) is still not capable in performing shortest route network analysis for 3D data. The complexity of building and surroundings makes GIS users require a system that can manage the phenomenon in 3D environment. Therefore, it is the aim of this study to conduct a research about the Dijsktra’s algorithm implementation for shortest path calculation in 3D environment. Hereby, the Dijkstra’s algorithm is tested with the developed 3D navigation network inside the building model. The results from the network analysis will be shown by using 3D computer game engine (3D State) in the 3D spatial objects environment and navigation can be made inside the 3D environment (Virtual Reality) by simulating human movements. Real texture of the surroundings is incorporated into the navigation system to produce realistic 3D surroundings and to give more 3D effects for the 3D virtual navigation.